PERAN GURU PAI DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA DI SDN PERMATA HIJAU KABUPATEN BANDUNG - Basnang Said; Beti Nurhayati; Reni Rohaeni; Seni Mukti (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
This research emerges as a response to the government's initiative to enhance the quality of human resources, aiming not only for competence but also grounded in the values of Pancasila. The study aims to gain a profound understanding of the role of Islamic Education teachers (PAI) in shaping the profiles of students with noble character in aspects of religious behavior, personal ethics, interactions with others, environmental ethics, and national ethics. Employing a descriptive method with a qualitative approach, data were collected through observation, interviews, and documentation. The research findings indicate that PAI teachers serve not only as educators but also as guides in instilling values of noble character based on the teachings of the Quran, Hadith, and the exemplary behavior of Prophet Muhammad. As a recommendation, collaboration with teachers of other subjects is crucial in shaping noble character, recognizing that the limited teaching time of PAI teachers may affect the effectiveness of instilling Pancasila-oriented student profiles.